Manajemen Transportasi Dinas Perhubungan Kota Bukittinggi - Fikra Hendra Fita (Jurnal Teori dan Riset Administrasi Publik, 2020)
This study aims to describe how the transportation management of the Bukittinggi City Transportation Agency. The background is that the City of Bukittinggi has received the Wahana Tata Nugraha award for the last 3 years, 2014-2016. The Wahana Tata Nugraha Award is an award given by the Government of the Republic of Indonesia to a city that is able to organize public transportation well. There are several activities that have been carried out well by the City of Bukittinggi City Transportation Service, including public transportation services, freight routes and special bus routes that are clear and equipped with traffic signs. Among these activities, there were problems with parking on the road and inadequate infrastructure. The method used in this research is descriptive qualitative. The data collection techniques used were interviews, observation, and documentation. The selection of informants was carried out by using purposive sampling technique. The data validity technique used in this study was the accidental sampling technique in accordance with the needs of the researcher and purposive sampling with certain considerations. The research analysis unit uses the institution. The results showed that the Transportation Management carried out by the Bukittinggi City Transportation Agency was basically going well.